The bad-ass librarians of Timbuktu : and their race to save the world's most precious manuscripts - Hammer, Joshua, 1957- (Simon & Schuster, 2016)
Describes how a group of Timbuktu librarians enacted a daring plan to smuggle the city's great collection of rare Islamic manuscripts away from the threat of destruction at the hands of Al Qaeda militants to the safety of southern Mali.